An Amalgamation of Postmodern elements; An Analysis of Ian McEwan's The Cement Garden as a postmodern Novel - et. al., S. Raja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ian McEwan is the best-known and controversial contemporary British novelist. McEwan seems to be interested in the relationship between reality and imagination, history and fabrication in the process of writing, which is generally considered as one of the themes related to postmodern metafiction writing. He also adopts the postmodern intertextuality in his writing practice. Those postmodern concerns and strategies confirm his position as a postmodernist. This paper is an attempt to bring out the various postmodern elements or strategies employed in his earlier novel The Cement Garden